Depiction of Slavery in Slave Narratives - Rokoská, Pavla (Univerzita Pardubice, 2013)
The aim of the bachelor thesis is to examine the issue of slavery in the United States in 1750-1870. The first part theoretically recounts the origins and development of the institution of slavery. The second part is based on the analysis of selected slave narratives reflecting direct experience of life in the bondage. The attention is focused especially on slaves' family life and relationships between slaves and slave owners. In conclusion, a comparison of the narratives and their importance for the abolitionist movement are discussed.
Zobrazení otroctví v životních příbězích otroků
Keywords: slavery; slaves; slave narratives; slave owners; otroctví; otroci; životopisy otroků; otrokáři